Exercise heat acclimation causes post-exercise hypotension and favorable improvements in lipid and immune profiles: A crossover randomized controlled trial. (August 2019) - Rivas, Eric; Crandall, Craig G.; Suman, Oscar E.; Moustaid-Moussa, Naima; Ben-Ezra, Vic
Abstract: Background: Passive hyperthermic exposure causes an acute hypotensive response following the cessation of heat stress. Chronic heat stress is well documented in animal studies to instigate metabolic and lipid alterations. However, it is unknown if exercise-heat acclimation also causes favorable chronic blood pressure, lipid, and immune responses in humans. Purpose: This project tested the hypothesis that 10-day exercise-heat acclimation (HA) would cause greater post-exercise reductions in arterial blood pressure and favorable metabolic, lipid, and immune responses compared to 10-day exercise under neutral conditions (CON). Methods: Thirteen healthy sedentary participants (8M/5F, 28 ± 6y, 78 ± 17 kg), completed a 10-day (90 min/day exercise bout) clamped hyperthermia HA (increase internal temperature 1.5 °C, in 42 °C, 28% R h ) and control (CON: 23 °C, 42% R h ) protocols in a counterbalanced design with a 2 month washout. Pre- and post-exercise HA/CON blood pressures were taken 1-h post-exercise on exercise days 1 and 10. Metabolic, lipid and immune panels were taken pre-post HA/CON. Results: Exercise under heat stress had greater post-exercise hypotension (systolic; -6 mmHg, diastolic; -8 mmHg; and mean arterial pressure; -7 mmHg) on both days 1 and 10 compared to exercise under neutral conditions (main effect for condition, P  ≤ 0.004). Only from pre-to-post HA, total cholesterol (168 ± 19 to 157 ± 15; P  < 0.03) and triglycerides (137 ± 45 to 111 ± 30; P  < 0.03) were reduced, while absolute lymphocytes (−26%), monocytes (−22%), and basophils (−49%) significantly decreased (each P  ≤ 0.04). Relative values of neutrophils increased (18%) and lymphocytes decreased (−20%) only after HA ( P  ≤ 0.04). Conclusion: These data indicate that exercise in the heat (regardless of acclimation status) causes a profound post-exercise hypotensive response, while HA causes favorable lipid, and immune profile changes. Further examination of exercise-heat acclimation on vascular, metabolic, and immune responses will offer insight for benefits in other clinical populations with vascular, metabolic and immune dysfunction. Highlights: It is unknown ifchronic heat exposure with exercise causes metabolic, lipid, vascular, and immune response in humans. We found that 10 day exercise-heat acclimation caused greater post-exercise hypotension after 1 and 10 days compared to exercise in neutral conditions. Exercise-heat acclimation also reduced lipid and immune profiles; however, these measures did not change after 10 days exercise in neutral conditions. Exercise-heat acclimation improves vascular, lipid, and immune profiles that may offer insight into benefits in clinical populations with vascular metabolic and immune dysfunction.